Acquired Inhibitors: A Special Case of Bleeding in Older Adults. (29th November 2012) - Stefanacci, Richard G.
Abstract : This literature review is intended to familiarize physicians and healthcare providers of older adults with the potential causes of acute bleeding in older adults and to review diagnostic approaches that can produce prompt identification of acute bleeding and facilitate timely treatment. Adverse events from anticoagulant treatment and nonsteroidal anti-inflammatory drug (NSAID) and aspirin use and abuse are among the most common causes of bleeding in older adults. Diagnoses infrequently considered—mild congenital hemophilia, acquired hemophilia, von Willebrand disease, and platelet dysfunction—can contribute to acute bleeding in older adults. The approach to management of bleeding varies. Management of acute bleeding in older adults can be challenging because these patients often have chronic comorbidity and have been prescribed long-term concomitant medications that can complicate diagnosis and treatment. Prompt recognition of acquired hemophilia, referral to an expert hematologist, and timely initiation of treatment could improve outcome in older patients who experience bleeding episodes resulting from this condition.